Analytical protocol for determination of endosulfan beta, propham, chlorpyrifos, and acibenzolar-s-methyl in lake water and wastewater samples by gas chromatography-mass spectrometry after dispersive liquid-liquid microextraction - Bodur, Suleyman; Ozlu, Cansu; Tisli, Busra; Firat, Merve; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2020)
This study describes the development of a sensitive and accurate dispersive liquid-liquid microextraction strategy for the preconcentration and determination of selected pesticides in wastewater and lake water samples by gas chromatography-mass spectrometry. Determination of these pesticides at high accuracy and precision is important because they can be still be found in environmental samples. The type of extraction solvent and type of disperser solvent were optimized using the univariate approach. Furthermore, a Box-Behnken experimental design was used to set up a working model made up of 18 combinations of three variables, tested at three levels. The parameters fitted into the design model were volume of extraction solvent, disperser solvent volume, and mixing period. Analysis of variance was used to evaluate the experimental data to determine the significance of extraction variables and their interactions, before selecting optimum extraction conditions. The method was then applied to aqueous standard solutions between 2.0 and 500 mu g L-1, and the limit of detection (LOD) and quantification (LOQ) values obtained for the analytes were between 0.37-2.8 and 1.2-9.4 mu g L-1, respectively. The percent recoveries were calculated in the range of 92-114 and 96-110% for wastewater and lake water, respectively. These results validated the accuracy and applicability of the method to the selected matrices.
Keywords: Dispersive liquid-liquid microextraction; Gas chromatography-mass spectrometry; Box-Behnken experimental design; Pesticides; BOX-BEHNKEN DESIGN; PESTICIDE CHLORPYRIFOS; EXTRACTION; ENVIRONMENT; QUECHERS; Environmental Sciences & Ecology